Preliminary Study on Developing Science Literacy Test for High School Students in Indonesia - Ariyanti, Ade Intan Permata; Ramli, Murni; Prayitno, Baskoro Adi (Sebelas Maret University, 2016)
The research aimed to describe the science literacy of high school student tested by Nature of Science Literacy Test (NOSLiT), which was developed by Carl J. Wenning. NOSLiT is a test to measure science literacy, as a research instrument to identify weaknesses of studentsâ understanding, and determine instrument effectiveness. NOSLiT consists of 35 multiple choice questions with four alternative answers, and true-false questions with two alternative answers. This study was begun with translating the original NOSLiT into Indonesian language, and validated the translated version by expert validators. Second, selected the respondents, consisted of 225 students from ten public and private high schools, i.e. 30 students of SMAN 1 Ngawi, 25 students of SMAN 2 Ngawi, 26 students MAN Ngawi, 21 students of SMAN Kwadungan, 25 students of SMA Muhammadiyah 1 Ngawi, 17 students of SMA Karya Pembangunan Paron, 29 students of SMAN 1 Madiun, 18 students of SMAN 3 Madiun, 23 students of SMAN 1 Nglames, and 11 students of SMA Cokro Aminoto Madiun. The result showed that the average score of NOSLiT test of grader X was 16.86; grader XI was 15.78; and grader XII was 16.40. Score of studentâs science literacy was quite low, or had not achieved at least 50% of total score, which put students into moderate literacy.